1993
DOI: 10.1002/for.3980120203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role judgment plays in forecast accuracy

Abstract: The majority of model-based forecasting efforts today rely on relatively simple techniques of estimation and the subjective adjustment of the model's results to produce forecasts. Published forecasts reflect to a great extent the judgment of the forecaster rather than what the model by itself has to say about the future. This paper examines the role judgment plays in the process of producing a macroeconometric forecast. The debate over the use of adjustment constants to alter the statistical results of a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…The decision-aid is to assist VCs, not replace them. In fact, there is evidence to suggest that a combination of human judgment and decision models results in more accurate decisions than either method alone (Whitecotton et al, 1998;Blattberg and Hoch, 1990;Donihue, 1993). While the research in this article takes an important step towards highlighting the importance of decision-aids for VCs, more research is required into the development of decisionaids and their use within VC firms.…”
Section: Decision-aids With Non-additive Relationshipsmentioning
confidence: 89%
“…The decision-aid is to assist VCs, not replace them. In fact, there is evidence to suggest that a combination of human judgment and decision models results in more accurate decisions than either method alone (Whitecotton et al, 1998;Blattberg and Hoch, 1990;Donihue, 1993). While the research in this article takes an important step towards highlighting the importance of decision-aids for VCs, more research is required into the development of decisionaids and their use within VC firms.…”
Section: Decision-aids With Non-additive Relationshipsmentioning
confidence: 89%
“…Interestingly, they showed that forecasters are more likely to adjust the forecasts that would have produced the largest forecast errors had the statistical forecasts remained unrevised. Other researchers have provided further evidence on the efficacy of judgmentally adjusted forecasts in macroeconomics (Donihue, 1993;McNees, 1990;Turner, 1990), accounting earnings (Brown, 1988) and business forecasting (Vere & Griffiths, 1995;Wolfe & Flores, 1990). Syntetos, Nikolopoulos, and Boylan (2010) showed that in addition to the improvements in performance as measured by traditional error metrics, judgmental adjustments of demand forecasts also result in significant reductions in inventory costs.…”
Section: Background Literaturementioning
confidence: 96%
“…The common factor in these studies is that when important domain knowledge is missing from the statistical forecasts, this can be integrated efficiently into the operational forecasts by applying judgmental adjustments to improve performance. However, two key elements affecting the success of an intervention are the reliability and importance of the missing information (Goodwin & Fildes, 1999) and the requirement that humans should not discount reliable statistical forecasts (Donihue, 1993).…”
Section: Background Literaturementioning
confidence: 99%
“…Evidence has accumulated that integrating such judgement with quantitative forecasts when the manager has access to information that has not been taken into account by the quantitative method leads to improved accuracy (e.g. see Donihue 1993, Mathews and Diamantopoulos ,1990, Goodwin and Fildes,1999. However, judgmental adjustments are also often applied unnecessarily, when the manager has no extra information to bring to the forecast, with deleterious effects on forecast accuracy O'Connor, 1995, Sanders andRitzman, 2001).…”
Section: The Integration Of Judgement With a Quantitative Modelmentioning
confidence: 99%